PENGARUH STATUS SOSIAL EKONOMI ORANG TUA TERHADAP SIKAP KEWIRAUSAHAAN - Ramadhanti, Dina; Mulyadi, Hari; Razati, Girang (Universitas Pendidikan Indonesia, 2016)
This study was conducted to determine whether there are significant socio-economic status of parents towards entrepreneurial attitudes. Data collected through questionnaires that have been tested for validity and reliability. The population in this study there was a class X student of marketing. Sampling on research using saturation sampling 71 respondents. Testing data in this study tested the validity, reliability test, linearity test and hypothesis testing. The method used is descriptive verification. Analysis data technique used is Partial Least Square with computer software tools SmartPLS 3.0. Based on this overall research result, the counting that gained from simple regression conclude that socio-economic status of parents have a positive impact with strong category towards entrepreneurial attitudes.Â Keywords: Socio Economic Status of Parents, Attitudes Entrepreneurship